Paleomagnetic inclinations and relative paleointensity variations during the upper Aptian to middle Albian in Sergipe-Alagoas Basin, South Atlantic Ocean (NE Brazil) - Gewehr De Mello, Raquel; Savian, Jairo; Gerson,Fauth; Satolli, Sara; Florindo, Fabio; Roisenberg, Henrique; Di Chiara, Anita; Leandro, Carolina; Lopes, Camila; Pontel, Caroline; Frigo, Everton; Santos, Alessandra; et al. (Geophysical Journal International, 2024)
During the Jurassic and Early Cretaceous, Earth's magnetic field experienced a high frequency of polarity reversals. This hyperactivity period is followed by a ∼38 Myr prolonged period of stable normal polarity from the Aptian until the Santonian, known as the Cretaceous Normal Superchron (CNS; chron C34n, from 121.4 to 83.65 Ma). Ho wever , the CNS might have been characterized by more variability than previously thought, but the current database is uneven in its spatial and temporal distribution. In this study, we integrate paleomagnetic and biostratigraphic data from the SER-03 sedimentary core, drilled onshore in the Sergipe-Alagoas Basin, NE Brazilian margin, South Atlantic Ocean. The 183-m cored interval spans 5.2 Myr (114.7-109.5 Ma), including the Aptian-Albian transition. It records the evolution from restricted marine settings to the complete opening of the South Atlantic Ocean. Magnetic remanence and rock magnetic parameters, such as magnetic susceptibility, anhysteretic remanent magnetization and isothermal remanent magnetization, were measured. Rock magnetic analyses indicated that primary magnetizations were preserved throughout the interval, with detrital magnetite identified as the primary magnetic carrier, predominantly in the pseudo-single domain and low-coercivity states. Normalizations by χ , ARM 15mT and IRM 15mT were used to determine relative paleointensity curves and were compared to the curve resulting from the pseudo-Thellier method. The SER-03 relative paleointensity record shows marked changes in both intensity and inclination. Inclination instability results are comparable with those found in volcanic rocks from surrounding the region. The high-resolution SER-03 magnetic record revealed that the field variability was higher than expected during the CNS, but remaining substantially lower than during other periods, such as the late Jurassic. The new SER-03 can serve as a dating and correlation tool for coe v al records. Published 1079–1095 OSA1: Variazioni del campo magnetico ...